The Role Of Midwives In Modern Obstetric Care: A Comprehensive Review (The Review of Diabetic Studies, 2024)
The role of midwives in modern obstetric care has evolved significantly, reflecting changes in societal expectations, healthcare policies, and advancements in medical knowledge. This comprehensive review examines the multifaceted contributions of midwives to maternal and neonatal health, emphasizing their critical involvement in prenatal care, labor support, postpartum care, and education. Midwives are trained professionals who provide holistic care, focusing on the physical, emotional, and social well-being of expectant mothers. Their approach often leads to improved maternal outcomes, including lower rates of cesarean sections and higher satisfaction among women regarding their childbirth experiences. This review also highlights various models of midwifery care, such as midwife-led care, collaborative care with obstetricians, and home birth options, illustrating the adaptability of midwifery practice to meet diverse patient needs. Despite the positive evidence supporting midwifery-led care, midwives face several challenges, including regulatory barriers, workforce shortages, and public misconceptions about their role. These challenges can limit their ability to provide optimal care and hinder the integration of midwifery services into mainstream obstetric practice. The review advocates for policy changes that support midwifery practice, increased funding for midwifery education, and public awareness campaigns to promote the benefits of midwifery care. Ultimately, the review underscores the importance of midwives as essential providers in modern obstetric care, advocating for their recognition and integration within healthcare systems. By highlighting the evidence supporting midwifery care and addressing the challenges faced by midwives, this review aims to contribute to the ongoing discourse on improving maternal and neonatal health outcomes and ensuring that women have access to comprehensive, supportive, and empowering care during pregnancy and childbirth.